Solid-state and aggregation-induced emission of novel bicyclic and tricyclic difluoroboron heterocycles - Žabenská, Martina; Capolungo, Chiara; Mariani, Chiara; Genovese, Damiano; Mikysek, Tomáš; Váňa, Jiří; Růžička, Aleš; Josefík, František; Svobodová, Markéta; Šimůnek, Petr (ROYAL SOC CHEMISTRY, 2024)
Six novel bicyclic and tricyclic difluoroboron NBN and OBN heterocycles were designed here in the quest for novel luminogenic molecular architectures because of their strong application potential as active layers in optoelectronics and as responsive units in sensing. They were prepared and then characterized with spectral (UV-vis, NMR, and luminescence) and electrochemical methods, and assessed via theoretical and X-ray investigations. Most of the compounds are non-emissive in solution, but luminescent in the solid state (red or yellow-green luminescence), and they are AIE active, offering excellent contrast for sensing schemes. Keeping this in view, two compounds were successfully embedded in Pluronic-silica nanoparticles (PluS NPs), coupling the AIEgenic properties of these compounds with the exceptional colloidal stability and functional surface of this type of nanostructure. Here, six novel bicyclic and tricyclic difluoroboron NBN and OBN heterocycles were designed for their strong potential as active layers in optoelectronics and responsive units in sensing applications.
Agregací indukovaná emise nových bicyklických a tricyklických difluoroboronových heterocyklů a jejich emise v pevném stavu
Keywords: AIE; difluoroboron heterocycles; nanoparticles; AIE; heterocykly s BF2 fragmentem; nanočástice